Singularity the polar of a plane branch in K(2p;2q;2q+d) - Hernández Iglesias, Mauro Fernando (2019)
We show that there is a Zariski open, in the set of plane branches with characteristic exponents 2p; 2q and 2q+d, wich is denoted by K(2p; 2q; 2q+d), with mcd{p,q} = 1 and d odd, where the polar is no degenerate, its topology is constant and determined only for p and q.